Improving Reading Comprehension Skills through the SQ3R Strategy in Primary School Students - Hakiki, Nurul; Guswita, Reni; Avana, Nurlev (FKIP - Universitas Riau, 2025)
Reading comprehension is one of the essential basic skills in primary school, although in reality many students still have difficulty understanding the content of texts. This study aims to improve the reading comprehension skills of fifth-grade students at SDN 91/VI Rantau Panjang VI through the Survey, Question, Read, Recite, Review (SQ3R) strategy. This study employs a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, conducted in two cycles, each cycle consisting of two meetings. Sixteen students and one fifth-grade teacher served as subjects in this study. Observations of teacher and student activities, as well as reading comprehension tests, were collected as data for this study and analyzed using descriptive statistical methods. The results of the study showed an increase in teacher activity from 73.98% in Cycle I to 88.40% in Cycle II, while student activity increased from 73.66% in Cycle I to 88.44% in Cycle II. The mean reading comprehension test scores also increased from 72.50 with a completion rate of 62.5% in Cycle I to 83.69 with a completion rate of 93.8% in Cycle II. These findings prove that the application of the SQ3R strategy is effective in improving primary school students' reading comprehension skills and encouraging their active involvement in the learning process.